Pengaruh Pemberian Sari Kacang Hijau terhadap Peningkatan Kadar Hemoglobin pada Remaja Putri di SMA Negeri 1 Menggala - Mutiara Rini Selviana; Rina Sri Widayati (Pusat Riset dan Inovasi Nasional, 2024)
Background : Adolescent girls are susceptible to anemia because they experience menstruation, where menstruation can cause a decrease in hemoglobin levels, thus requiring special attention to iron needs. The results of the 2021 Riskesdas showed an increase in the rate of anemia in adolescents with a female sample of 22.7%. The effort taken is to drink green bean juice because it contains iron and vitamin C which helps increase hemoglobin levels. Objective : to determine the effect of giving Green Bean Juice on increasing Hemoglobin levels in adolescent girls. Method : The research design was Pre Experiment and One Group Pretest Posttest approach, a sample of 20 young women from class XI, the sample used was random sampling. Test the analysis using the Paired Simple T Test. Research results : The results of the Paired Simple T Test based on the Hb value before and after treatment showed a significant value of 0.000 < 0.05 with an average increase of 1.2 gr/dl. Conclusion : There is an effect of giving Green Bean Juice on increasing Hemoglobin levels in young women at SMA Negeri 1 Menggala Tulang Bawang.